Comparing Bleeding and Thrombotic Rates in Spine Surgery: An Analysis of 119 888 Patients. Issue 2 (March 2021) - Pirkle, Sean; Cook, David J.; Kaskovich, Samuel; Bhattacharjee, Sarah; Ho, Alisha; Shi, Lewis L.; Lee, Michael J.
Study Design: Retrospective, database review. Objectives: Examine the utilization rate of postoperative deep vein thrombosis (DVT) prophylaxis and compare the incidence and severity of bleeding and thrombotic complications in elective spine surgery patients. Methods: We utilized PearlDiver, a national orthopedics claims database. All patients who underwent elective spine surgery from 2007 to 2017 were included. Patients were stratified by the presence of DVT prophylaxis drug codes, then by comorbidities for postoperative bleeding/thrombosis. The severity of all bleeding and thrombotic complications in each cohort was studied, including the incidence of complications requiring operative washout, diagnosis of pulmonary embolism, intensive care unit admission, and mortality. Results: A total of 119 888 patients were included. The majority of patients (118 720, >99%) were not administered postoperative DVT chemoprophylaxis while a minority of patients (1168) were. The overall rates of bleeding and thrombotic complications within the population not receiving DVT prophylaxis were 1.96% and 2.45%, respectively ( P < .001). The incidence of surgical intervention for a wound washout was 0.62% compared with 1.05% for pulmonary embolism ( P < .001). Intensive care unit admission rates related to a wound washout procedure or pulmonary embolism also significantly differed (0.07% vs 0.34%, P < .001). There were no observed differences in mortality. When controlling for patient comorbidity, patients with atrial fibrillation, cancer, or a prior history of thrombotic complications experienced the greatest increased risks of postoperative thrombosis. Conclusions: DVT prophylaxis is not routinely utilized following elective spine procedures. We report that there exist specific populations which may receive benefit from these practices, although further study is necessary to determine optimal prevention strategies for both thrombotic and bleeding complications in spine surgery.